Bibliometric study on the Pedagogy of Alternance in scientific articles (1981-2019) (Praxis Educativa, 2022)
Pedagogy of Alternation (PA) is a formative and educational proposal of the human being that organizes the teaching-learning process, alternating spaces between family property and school. This study aims to understand how the current state of knowledge on this theme is configured, through the methodology of bibliometric and content analysis. The data source was articles indexed on the Web of Science, Scopus, Redalyc, DOAJ, SciELO, Educ @, EDUBASE, Portal de Periódicos Capes. The selected articles (n = 251) were published between 1981 and 2019, and analyzed according to the categories of: temporality, authors and authorship, profile of journals, typology of articles, locus and objects of study of empirical research, scope of theoretical essays and critical analysis of meta-analyzes. The results made it possible to identify the longitudinal and structural perspectives of scientific production in Pedagogy of Alternation and their links with various disciplinary and interdisciplinary contexts.
Keywords: Pedagogy of Alternation; state of knowledge; scientific production; bibliometric content analysis